2008
DOI: 10.1002/jssc.200700399
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of biogenic amines in human plasma based on the derivatization with N‐hydroxy‐succinimidyl fluorescein‐O‐acetate by high‐performance liquid chromatography

Abstract: An HPLC method for the determination of biogenic amines based on the precolumn derivatization with N-hydroxysuccinimidyl fluorescein-O-acetate (SIFA) has been developed. The derivatization was performed at 45 degrees C for 30 min in borate buffer (pH 8.0). The derivatives were separated on a ZORBAX Eclipse XDB-C8 column (150 mm x 4.6 mm id; 5 mum) and monitored by fluorescence detection (excitation, 469 nm; emission, 512 nm). The LODs (S/N = 3) for spermine, spermidine, putrescine, cadaverine, and phenethylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…There are many derivatization reagents usually applied for biogenic amines analysis such as bis-3,5-dinitrobenzoyl chloride (DNBZ-Cl) [13], dabsyl chloride (Dbs-Cl) [14], benzoyl chloride [15], 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) [16], [2-ethylhexyl] sulphosuccinate (AOT) [17], dansyl chloride (Dns-Cl) [18], 9-fluorenylmethyl chloroformate (FMOC) [19], o-phthalaldehyde (OPA) [20], N-hydroxysuccinimidyl fluorescein-o-acetate (SIFA) [21], 1,2-naphthoquinone-4-sulfonate (NOS) [22] and 4-chloro-3, 5-dinitrobenzotrifluoride (CNBF) [23]. In spite of the popularity of these pre-column methods, there have also been many reports describing various shortcomings in their applications, such as short detection wavelengths, poor reproducibility and stability, redundant hydrolysates, incomplete reactions and serious interference for the determination of real samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many derivatization reagents usually applied for biogenic amines analysis such as bis-3,5-dinitrobenzoyl chloride (DNBZ-Cl) [13], dabsyl chloride (Dbs-Cl) [14], benzoyl chloride [15], 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) [16], [2-ethylhexyl] sulphosuccinate (AOT) [17], dansyl chloride (Dns-Cl) [18], 9-fluorenylmethyl chloroformate (FMOC) [19], o-phthalaldehyde (OPA) [20], N-hydroxysuccinimidyl fluorescein-o-acetate (SIFA) [21], 1,2-naphthoquinone-4-sulfonate (NOS) [22] and 4-chloro-3, 5-dinitrobenzotrifluoride (CNBF) [23]. In spite of the popularity of these pre-column methods, there have also been many reports describing various shortcomings in their applications, such as short detection wavelengths, poor reproducibility and stability, redundant hydrolysates, incomplete reactions and serious interference for the determination of real samples.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines are usually determined by thin layer chromatography (TLC) [6,7], capillary electrophoresis (CE) [8][9][10], gas chromatography (GC) [11,12] and liquid chromatography (LC) with ultra-violet (UV) or fluorescence detection [13][14][15][16][17][18][19][20][21][22][23]25]. Among these methods, LC is the most popular and frequently used for the separation and quantification of biogenic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines are usually determined by separation techniques like thin layer chromatography (TLC) [22][23][24], capillary electrophoresis (CE) [17,[25][26][27][28][29], gas chromatography (GC) [30][31][32][33][34] and High performance liquid chromatography (HPLC) [21,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. HPLC is the technique most extensively used due to its high resolution, sensitivity, great versatility, and simple sample treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Du et al showed that a fluorescein backbone is gaining growing popularity for HPLC applications where they synthesised a 6-oxy-(acetyl ethylenediamine)fluorescein derivative and successfully labelled 12 fatty acids. Deng et al also prepared a fluorescein derivative, namely N-hydroxy-succinimidyl fluorescein-O-acetate and applied it to quantitate biogenic amines with impressive 0.2-0.4 nM limits of detection [15,16].…”
Section: Introductionmentioning
confidence: 98%